Genome-Wide Identification of the TIFY Family in Salvia miltiorrhiza Reveals That SmJAZ3 Interacts With SmWD40-170, a Relevant Protein That Modulates Secondary Metabolism and Development - Li, Lin; Liu, Yuanchu; Huang, Ying; Li, Bin; Ma, Wen; Wang, Donghao; Cao, Xiaoyan; Wang, Zhezhi (Frontiers in Plant Science, 2021)
Salvia miltiorrhiza Bunge (S. miltiorrhiza), a traditional Chinese medicinal herb, contains numerous bioactive components with broad range of pharmacological properties. By increasing the levels of endogenous jasmonate (JA) in plants or treating them with methyl jasmonate (MeJA), the level of tanshinones and salvianolic acids can be greatly enhanced. The jasmonate ZIM (JAZ) proteins belong to the TIFY family, and act as repressors, releasing targeted transcriptional factors in the JA signaling pathway. Herein, we identified and characterized 15 TIFY proteins present in S. miltiorrhiza. Quantitative real-time PCR analysis indicated that the JAZ genes were all constitutively expressed in different tissues and were induced by MeJA treatments. SmJAZ3, which negatively regulates the tanshinones biosynthesis pathway in S. miltiorrhiza and the detailed molecular mechanism is poorly understood. SmJAZ3 acts as a bait protein to capture and identify a WD-repeat containing the protein SmWD40-170. Further molecular and genetic analysis revealed that SmWD40-170 is a positive regulator, promoting the accumulation of secondary metabolites in S. miltiorrhiza. Our study systematically analyzed the TIFY family and speculated a module of the JAZ-WD40 complex provides new insights into the mechanisms regulating the biosynthesis of secondary metabolites in S. miltiorrhiza.